Melatonin in Arabidopsis thaliana acts as plant growth regulator at low concentrations and preserves seed viability at high concentrations - Gatica Hernandez, Ismaél Jairo Gabriel (2015)
Since the discovery of melatonin in plants, several roles have been described for different species, organs, and developmental stages. Arabidopsis thaliana, being a model plant species, is adequate to contribute to the elucidation of the role of melatonin in plants. In this work, melatonin was monitored daily by UHPLC-MS/MS in leaves, in order to study its diurnal accumulation as well as the effects of natural and artificial light treatments on its concentration. Furthermore, the effects of exogenous application of melatonin to assess its role in seed viability after heat stress and as a regulator of growth and development of vegetative tissues were evaluated. Our results indicate that melatonin contents in Arabidopsis were higher in plants growing under natural radiation when compared to those growing under artificial conditions, and its levels were not diurnally-regulated. Exogenous melatonin applications prolonged seed viability after heat stress conditions. In addition, melatonin applications retarded leaf senescence. Its effects as growth promoter were dose and tissue–dependent; stimulating root growth at low concentrations and decreasing leaf area at high doses.